2022
DOI: 10.1002/acn3.51650
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase predicting mortality in patients with aneurysmal subarachnoid hemorrhage

Abstract: Objective Lactate dehydrogenase (LDH) has been reported to be associated with outcomes after surgery in patients with aneurysmal subarachnoid hemorrhage (aSAH), but it is unclear if this is independent from other biomarkers and across all aSAH treatments. This study aims to assess whether LDH is an independent predictor of mortality in patients with aSAH and test whether the inclusion of LDH in a well‐established prediction model can improve discrimination and reclassification. Methods This was a retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Consistent with previous studies on acute cerebral hemorrhage ( 13 ), on the other hand, we support the hypothesis that serum SAA concentrations can reflect the clinical severity after acute brain injury, including acute cerebral hemorrhage and aSAH. Our study revealed that serum SAA was independently associated with 90-day poor outcome even after correcting for conventional prognostic determinants, such as WFNS scores and modified Fisher scores, which are the two common determinants for prognosis of aSAH ( 8 , 31 33 ). In addition, under ROC curve, serum SAA concentrations showed significant prognostic accuracy in differentiating patients with poor prognosis from those with good prognosis at 3 months after aSAH.…”
Section: Discussionmentioning
confidence: 68%
“…Consistent with previous studies on acute cerebral hemorrhage ( 13 ), on the other hand, we support the hypothesis that serum SAA concentrations can reflect the clinical severity after acute brain injury, including acute cerebral hemorrhage and aSAH. Our study revealed that serum SAA was independently associated with 90-day poor outcome even after correcting for conventional prognostic determinants, such as WFNS scores and modified Fisher scores, which are the two common determinants for prognosis of aSAH ( 8 , 31 33 ). In addition, under ROC curve, serum SAA concentrations showed significant prognostic accuracy in differentiating patients with poor prognosis from those with good prognosis at 3 months after aSAH.…”
Section: Discussionmentioning
confidence: 68%
“…In 1978, Rao et al [ 17 ] described that serum LDH levels were directly proportional to the clinical (level of consciousness) and radiological severity of brain injury, possibly representing the extent of brain damage in head injury patients. More recently, Zan et al [ 20 ] in a retrospective study, have shown that LDH level on admission is an independent predictor of all-cause mortality in patients with SAH. In their analysis, the authors showed that for each 1-point increase in LDH, the chance of 90-days of mortality increase of 1.98 (95% CI 1.30- 3.20).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high serum LDH values have been associated with the extend of cerebral damage in acute brain injured patients [ 17 ]. Recently, in a population of aSAH patients, high serum LDH values before microsurgical clipping were associated with poor neurological outcome at 3 months [ 18 ]; in a similar cohort, high serum LDH values on hospital admission were associated with the development of post operative pneumonia (POP) [ 19 ]; finally, in another cohort of aSAH patients, high serum LDH values were associated with early mortality [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated serum LDH during hospitalization was positively related with in-hospital mortality in patients with acute aortic dissection [17]. In patients with aneurysmal subarachnoid hemorrhage, the LDH level is an independent predictor of allcause mortality [18]. High serum LDH levels predicted unfavorable clinical outcomes after intravenous thrombolysis in acute ischemic stroke patients [19].…”
Section: Introductionmentioning
confidence: 99%